Teachers' Understanding of and Preparedness to Implement Response to Intervention (Rtl) - Kapfhamer, Alyssa (My University, 2009)
With the 2004 reauthorization of the Individuals with Disabilities Act (IDEA), school districts have the option of using Response to Intervention (RtI) to provide services to struggling learners. This current study utilizes a questionaire to examine teachers' understandings of their new roles under Rtl, how prepared they believe they are for their new responsibilities, and what kind of assistance they might need to implement Rtl.
Color poster with text and graphs (Spring 2009)
Keywords: Posters; Response to Intervention (Rtl); Teachers--Attitudes; Learning disabled children--Education; Remedial teaching; Slow learning children--Education